(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
The Messina genesis of the dual vocation of Giorgio La Pira, a scholar of Roman law and Venerable of the Catholic Church ABSTRACT: In the same Messina environment in which the religious conversion of the young La Pira grew, his vocation as a historian of Romanity was also defined as being able to gather the typical unity profile with respect for the diversity of faiths and Mediterranean cultures. Therefore, it is not surprising that Pope Francis, once the "Holy Mayor of Florence" was proclaimed Venerable, agreed with him in recognising the Mediterranean as a place of communication between different worlds. 1 - Un rigoroso pensatore teutonico, Ludwig Wittgenstein, della cui dottrina, pur nel dissenso, non può non farsi carico ogni serio ambito di studi, ha enunciato, fra gli altri, due asserti piuttosto allarmanti in ordine a quanto ci si prefigge di trattare, e cioè: a) che il passato non ci direbbe molto del presente e b) che quando non si ha una conoscenza logico-empirica, cioè fondata sull’esperienza sensibile, sarebbe meglio tacere. (continua)